Razvoj družinskih centrov v Sloveniji - Narat, Tamara (Socialno delo, 2012)
The article addresses the perception of Slovene municipalities of their role in ensuring the quality of life of families with children, their knowledge about activities of family centres according to the current definition set by Ministry of Labour, Family and Social Affairs, and their attitude towards these centres. The main focus of the article is given to the analysis of municipalities' perspective towards establishment of family centres based on the models operating abroad - for non-Slovene centres it is caracteristique that they provide the place that enables socializing and integration, and that they are strongly embedded in local communities. Here particularly the needs and interests of municipalities and their role in potential implementation of family centres are being investigated. The article is based on the analysis of representative sample of representatives of 141 municipalities and on the analysis of 10 semi-structured interviews among selected municipalities. The obtained results show that municipalities support the idea of family centres - they recognize the possibility for integration and upgrading the existing institutions that offer these kind of services. Concerning the implementation of family centres, analysed data implicates that the majority of municipalities are prepared to take an active role in this field in cooperation with the government.
Keywords: Family; Kakovost življenja; standard of living; Lokalne skupnosti; Family policy; Quality of life; Slovenija; Local communities; družina; družinska politika; Slovenia; kvaliteta življenja